Valine-Glutamine Proteins in Plant Responses to Oxygen and Nitric Oxide - José León (Frontiers in Plant Science, 2021)
Multigene families coding for valine-glutamine (VQ) proteins have been identified in all kind of plants but chlorophytes. VQ proteins are transcriptional regulators, which often interact with WRKY transcription factors to regulate gene expression sometimes modulated by reversible phosphorylation. Different VQ-WRKY complexes regulate defense against varied pathogens as well as responses to osmotic stress and extreme temperatures. However, despite these well-known functions, new regulatory activities for VQ proteins are still to be explored. Searching public Arabidopsis thaliana transcriptome data for new potential targets of VQ-WRKY regulation allowed us identifying several VQ protein and WRKY factor encoding genes that were differentially expressed in oxygen-related processes such as responses to hypoxia or ozone-triggered oxidative stress. Moreover, some of those were also differentially regulated upon nitric oxide (NO) treatment. These subsets of VQ and WRKY proteins might combine into different VQ-WRKY complexes, thus representing a potential regulatory core of NO-modulated and O2-modulated responses. Given the increasing relevance that gasotransmitters are gaining as plant physiology regulators, and particularly considering the key roles exerted by O2 and NO in regulating the N-degron pathway-controlled stability of transcription factors, VQ and WRKY proteins could be instrumental in regulating manifold processes in plants.